Is it
(sec x/(csc x - cot x) - (sec x/(csc x + cot x))= 2 csc x or
sec x/csc x - cot x - sec x/csc x + cot x= 2 csc x
The way you typed it, according to order of operation, it would be that last one, but that is not an identity.
so
(sec x/(csc x - cot x) - (sec x/(csc x + cot x))= 2 csc x
LS = (secxcscx + secxcotx - secxcscx + secxcotx)/(csc^2x - cot^2x)
= 2secxcotx/(csc^2x - (csc^2x - 1))
= 2(1/cosx)(cosx/sinx)
= 2/sinx
= 2cscx
= RS
can someone please show me how to verify this identity?
(sec x/csc x minus cot x) minus (sec x/csc x + cot x)= 2 csc x
3 answers
Need some help with this: find all solutions of cot^2 x=3 in the interval [0,2pi)
Verify the Identity for (1-tanx)^2 = sec^2x-2tanx